Triple Threat: HDV, HBV, HIV Coinfection - Yen, Debra W.; Soriano, Vicente; Barreiro, Pablo; Sherman, Kenneth E. (Clinics in Liver Disease, 2024)
First discovered in the late 1970s, hepatitis delta virus (HDV) has emerged as an important driver of decompensated liver disease and hepatocellular carcinoma (HCC) worldwide. HDV requires hepatitis B virus (HBV) for transmission and occurs as either a coinfection with HBV or a superinfection in the setting of chronic HBV. The global prevalence is difficult to estimate, but HDV likely affects around 15 to 25 million people worldwide. Due to shared transmission routes, namely sexual and parenteral, people living with HIV (PLWH) often are coinfected by HBV, HDV, and hepatitis C virus (HCV). Despite the severe disease course and rapid progression of liver disease with HDV, it remains underdiagnosed, including in the HIV population. Fortunately, novel therapies are forthcoming although studies
Keywords: HIV; VIH; hepatitis delta; HDV; viral hetatitis; coinfection; liver disease; Scopus; JCR